PERKEMBANGAN DESA WISATA KARANGBANJAR - , BAYU YUDIARTO R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is motivated by the declining trend in tourism activities in Karangbanjar Tourism Village, which has established since 1992. However, this decline is coupled with the increasing hair craft which becomes the main attraction in this tourism village. The purpose of this study is to identify the trends in the development of Karangbanjar tourism village from 1992 to 2013 and to find the cause of the decline in the tourism sector in the tourist village. The method used was deductive qualitative. The level of development of the tourism village was seen from three aspects: economic, social and physical environment. The factors causing the decline in the tourism sector were exploratory explored in order to obtain in-depth information. The data were collected using observation, interviews and secondary data collection. The data were analyzed using data reduction, then the validity of the data was tested using triangulation techniques. The results showed that the Karangbanjar Tourism Village today is less developed. From the economic aspect, there is no additional income for the villagers. From the social aspect, the citizens do not have proficient skills in presenting and managing tourism village. But the progress is good enough as what can be seen from the physical aspects of the environment such as adequate homestay, conference hall facilities and any additions can appeal, although there are not able to optimally attract tourists. The factors causing the decline in the tourism sector in the Karangbanjar Tourism Village are: (1) the decrease of the enthusiasm and participation of the villagers, (2) the policy issues of the government of Purbalingga, (3) the lack of ability of the human resources in charge of managing Karangbanjar Tourism Village, and (4) Owabong and Sanggaluri Park emerge as competitors.